The Effect of Alkaline Pretreatment Methods on Cellulose Structure and Accessibility. Issue 2 (24th November 2014) - Bali, Garima; Meng, Xianzhi; Deneff, Jacob I.; Sun, Qining; Ragauskas, Arthur J.
Abstract The effects of different alkaline pretreatments on cellulose structural features and accessibility are compared and correlated with the enzymatic hydrolysis of Populus. The pretreatments are shown to modify polysaccharides and lignin content to enhance the accessibility for cellulase enzymes. The highest increase in the cellulose accessibility was observed in dilute sodium hydroxide, followed by methods using ammonia soaking and lime (Ca(OH)2). The biggest increase of cellulose accessibility occurs during the first 10 min of pretreatment, with further increases at a slower rate as severity increases. Low temperature ammonia soaking at longer residence times dissolved a major portion of hemicellulose and exhibited higher cellulose accessibility than high temperature soaking. Moreover, the most significant reduction of degree of polymerization (DP) occurred for dilute sodium hydroxide (NaOH) and ammonia pretreated Populus samples. The study thus identifies important cellulose structural features and relevant parameters related to biomass recalcitrance.